PENINGKATAN PEMAHAMAN DAN KEMAMPUAN BERPENDAPAT SISWA PADA KOMPETENSI TSUNAMI MENGGUNAKAN PEMBELAJARAN NHT - Haryati, Ani (Vidya Karya Jurnal Kependidikan, 2013)
The studentâs interest in learning Tsunami material in SMK Banua Lawas 1 is low, therefore it is below the standard classical completeness. This study aims to (1) Improve student comprehension, (2) Enhance the ability of the students argued, (3) Knowing the studentsâ responses. Research design used a class action research with 2 cycles. The subjects were 29 students of grade XC SMK 1 Banua Lawas, Tabalong. The research instrument is observation sheet, questionnaire responses and student achievement test. Results showed (1) student comprehension increases from 68.1 in the first cycle to 81.72 in the second cycle. Mastery learning classical increases from 62.10% in the first cycle to 96.6% in the second cycle. (2) student ability to give opinion increases from âgoodâ category (34.5%) to âvery goodâ category (82.8%), (3) studentsâ positive response increases from âvery goodâ category (41% or 12 students ) and âgoodâ category (59% or 17 students) into âvery goodâ category (69% or 20 students) and âgoodâ category (31%).